2011
DOI: 10.1186/1471-2415-11-19
|View full text |Cite
|
Sign up to set email alerts
|

The direction of research into visual disability and quality of life in glaucoma

Abstract: BackgroundGlaucoma will undoubtedly impact on a person's ability to function as they go about their day-to-day life. The purpose of this study is to investigate the amount of published knowledge in quality of life (QoL) and visual disability studies for glaucoma, and make comparisons with similar research in other chronic conditions.MethodsA systematic literature search of the Global Health, EMBASE Psychiatry and MEDLINE databases. Title searches for glaucoma and six other example chronic diseases were entered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 40 publications
0
31
0
4
Order By: Relevance
“…This isn't surprising because untangling the visual component from all the other factors that contribute to everyday visually guided tasks such as mobility, driving, searching for items, recognising faces, and reading is difficult to do. Nevertheless, the research activity devoted to this challenge is insufficient; 7 this is a pity, because meaningful landmarks for disease progression in glaucoma would help in managing patients. Furthermore, the benchmark for a new treatment success in a clinical trial should really be aligned to measureable reduction in visual disability rather than often imperceptible changes on a clinical visual field or visual acuity chart.…”
Section: Introductionmentioning
confidence: 99%
“…This isn't surprising because untangling the visual component from all the other factors that contribute to everyday visually guided tasks such as mobility, driving, searching for items, recognising faces, and reading is difficult to do. Nevertheless, the research activity devoted to this challenge is insufficient; 7 this is a pity, because meaningful landmarks for disease progression in glaucoma would help in managing patients. Furthermore, the benchmark for a new treatment success in a clinical trial should really be aligned to measureable reduction in visual disability rather than often imperceptible changes on a clinical visual field or visual acuity chart.…”
Section: Introductionmentioning
confidence: 99%
“…QoL in patients with glaucoma and AMD were shown to be impaired, with multiple daily activities being more difficult to perform compared with normal individuals. [4][5][6][7][8]18,[28][29][30] Several studies have investigated vision-related QoL in patients with glaucoma and AMD. 7,14-21,31-36 They revealed that total scores of general sighted population was significantly higher compared with AMD or POAG patients.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were reported in the literature. 30,[38][39][40] In the current study, results of 24-2 SITA and 10-2 SITA visual field tests were used to provide an objective measure to evaluate the impact of field changes on QoL. MD values of Humphrey 24-2 SITA visual field tests were found to be significantly lower in patients with POAG than those with AMD.…”
mentioning
confidence: 88%
“…A fundamental part of assessing clinical effectiveness involves measuring quality of life (QOL). Although there is now increasing interest in the QOL of glaucoma sufferers, less than 2% of all glaucoma studies have focused on QOL (Glen et al 2011). A number of QOL papers have shown that even in early glaucoma some patients do experience limitations in their vision (Viswanathan et al 1999, Janz et al 2001, Nelson et al 2003, Goldberg et al 2009) and these studies have also reported that patients have difficulties with dark adaptation and disability glare.…”
Section: Introductionmentioning
confidence: 99%